If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2x + -4(x + -3) = 15 Reorder the terms: 2x + -4(-3 + x) = 15 2x + (-3 * -4 + x * -4) = 15 2x + (12 + -4x) = 15 Reorder the terms: 12 + 2x + -4x = 15 Combine like terms: 2x + -4x = -2x 12 + -2x = 15 Solving 12 + -2x = 15 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-12' to each side of the equation. 12 + -12 + -2x = 15 + -12 Combine like terms: 12 + -12 = 0 0 + -2x = 15 + -12 -2x = 15 + -12 Combine like terms: 15 + -12 = 3 -2x = 3 Divide each side by '-2'. x = -1.5 Simplifying x = -1.5
| 4x^2-52x+153=0 | | 9y-2y=5(y-4) | | 3x^2*(x^2-1)-x^3*2x=0 | | 2u^2-7u+3=2 | | 7x+5=3x+18 | | x=156+0.6x | | x(2x^2-32)=0 | | 100-8y=60 | | 3a-6=a-4 | | 6logx+2=0 | | z^6=27 | | 3=1+0.5v | | 2r+9=r+15 | | z^2+16+30i=0 | | 0.05(500)+40=0.07(500)+30 | | x^3=0.75 | | f(x)=x^3+13x^2+36x | | x^3+6x^2+11x-6=0 | | 0.05x+40=0.07x+30 | | 2u^2-7u-11=0 | | -80-12.2= | | 36=x-50 | | 7x=2x+-35 | | 10=a*1 | | 3(2m-1)+5=6(m+1) | | 3(2m-1)=6(m+1) | | 2y=8-2x | | y=-1E-05x+0.004 | | 3y-11=7 | | 2x+300=5x | | X(x-2)=-2x | | 5x+1=2x+17 |